Oropharyngeal Dysphagia as The Presenting Symptom of Myasthenia Gravis with Diabetes Mellitus - Handy Kurnia; Heri Nugroho Hario Seno; Aris Catur Bintoro; Hery Djagat Purnomo (Medica Hospitalia : Journal of Clinical Medicine, 2024)
Background: Oropharyngeal dysphagia may caused by a variety of causes. Myasthenia gravis is a common autoimmune disease affecting the neuromuscular junction. While ocular symptoms are common in myasthenia gravis, bulbar symptoms such as dysarthria and dysphagia are less common. Aim: To present the importance of recognizing atypical presentations of myasthenia gravis and utilizing electromyography in diagnosis when AChR antibody testing is unavailable. Case Presentation: A 57-year-old woman was referred because of progressive dysphagia for both solid and liquid food. She also experienced weight loss, heaviness of the right eyelid, drooling, and chewing difficulty. Medical history revealed diabetes. Vital signs were stable. Physical examination revealed right ptosis without any other neurological deficits. Wartenberg test and dysarthria counting test were positive. Laboratory examination revealed a blood glucose level of 270 mg/dL and an HbA1c level of 9.4%. The barium swallow study revealedno abnormalities. Esophagogastroduodenoscopy revealed esophageal candidiasis. Electromyography showed more than 20% decremental response of the orbicularis oculi muscle. This result is suggestive of neuromuscular junction disorder. Improvement of the condition was achieved after the administration of intravenous steroids and oral pyridostigmine combined with therapeutic plasma exchange. Discussion: Oropharyngeal dysphagia accompanied by ptosis and positive Wartenberg & dysarthria counting test is suggestive of myasthenia gravis. Although an AChR antibody test cannot be performed, significant electromyography alongside relevant clinical presentation is sufficient to diagnose myasthenia gravis. Conclusion: It is crucial to recognize the accompanying signs and symptoms of oropharyngeal dysphagia. EMG may be used to diagnose MG in the appropriate clinical context.